2020
DOI: 10.1101/2020.03.31.018416
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of soil depth on the structure of microbial communities in agricultural soils in Iowa, USA

Abstract: 17 The determination of how microbial community structure changes within the soil profile, 18 will be beneficial to understanding the long-term health of agricultural soil ecosystems 19 and will provide a first step towards elucidating how deep soil microbial communities 20 contribute to carbon sequestration. This study aimed to investigate the differences in the 21 microbial community abundance, composition and diversity throughout from the surface 22 layers down to deep soils in corn and soybean fields in Io… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 60 publications
(59 reference statements)
6
11
0
Order By: Relevance
“…2 ). These findings are in concordance with the previous studies that soil depth plays an important role to shape the soil bacterial communities owing to differences in soil properties [ 7 , 37 ]. Although soil properties (e.g., pH, AP, AK, AN) along different soil depths varied from each other but resulted in a high percentage of the shared OTUs accounted for 93.8% of total reads and it implies that similarity of bacterial community composition was high along the soil gradient.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…2 ). These findings are in concordance with the previous studies that soil depth plays an important role to shape the soil bacterial communities owing to differences in soil properties [ 7 , 37 ]. Although soil properties (e.g., pH, AP, AK, AN) along different soil depths varied from each other but resulted in a high percentage of the shared OTUs accounted for 93.8% of total reads and it implies that similarity of bacterial community composition was high along the soil gradient.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, the relative abundance of Acidobacteria and Actinobacteria varied throughout the soil depth in one previous study [ 43 ]. However, we found that the RA of Acidobacteria was decreased with increasing soil depth, whereas Actinobacteria RA was at the peak in RS3 (40–60 cm), and consistent with the previous results where similar trends were observed in agricultural soils of Iowa, USA [ 7 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…To study the bacterial communities in the rhizosphere and root endosphere collected from greenhouse experiment three, the V4 region of the 16S rRNA gene was amplified and sequenced with Illumina MiSeq platform using the protocol described in Hao et al (2021). The resulting sequencing data were processed and analysed using the UPARSE pipeline (Edgar, 2013) and QIIME (version 1.9.1 and 2) (Bolyen et al, 2019;Caporaso et al, 2010).…”
Section: Sequencing and Data Analysismentioning
confidence: 99%